Phosphoinositide-3-Kinase Activation Controls Synaptogenesis and Spinogenesis in Hippocampal Neurons - Cuesto, Germán (J Neurosci, 2011)
The possibility of changing the number of synapses may be an important asset in the treatment of neurological diseases. In this context, the synaptogenic role of the phosphoinositide-3-kinase (PI3K) signaling cascade has been previously demonstrated in Drosophila. This study shows that treatment with a PI3K-activating transduction peptide is able to promote synaptogenesis and spinogenesis in primary cultures of rat hippocampal neurons, as well as in CA1 hippocampal neurons in vivo. In culture, the peptide increases synapse density independently of cell density, culture age, dendritic complexity, or synapse type. The induced synapses also increase neurotransmitter release from cultured neurons. The synaptogenic signaling pathway includes PI3K-Akt. Furthermore, the treatment is effective on adult neurons, where it induces spinogenesis and enhances the cognitive behavior of treated animals in a fear-conditioning assay. These findings demonstrate that functional synaptogenesis can be induced in mature mammalian brains through PI3K activation.